Trades access common core. Line A, Safe work practices, Competency A-2, Describe WorkSafeBC regulations - Lidstone, Rod; Camosun College; British Columbia. Ministry of Technolgy, Innovation and Citizens' Services; BC Open Textbook Project; BCcampus (Ministry of Technology, Innovation and Citizens' Services, 2015)
" In most provinces, one or more agencies are responsible for safe, healthful working environments at job sites. These organizations normally have names such as the Workers' Compensation Board (WCB) or the Occupational Health and Safety Department. WorkSafeBC is the provincial organization that promotes workplace health and safety for workers and employers in BC. When a work-related injury, disease, or death occurs, WorkSafeBC collaborates with those involved to provide return-to-work rehabilitation, health-care benefits, compensation, and a range of other services. WorkSafeBC also consults with and educates employers and workers on safe work practices. This includes monitoring workplaces within its jurisdiction. The following list of lines and competencies was generated with the goal of creating an entry-level trades training resource, while still offering the flexibility for lines to be used as stand-alone books. Line A Books include: A-1 Control Workplace Hazards, A-2 Describe WorkSafeBC Regulations, A-3 Handle Hazardous Materials Safely, A-4 Describe Personal Safety Practices, A-5 Describe Fire Safety."--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
"Copyright Camosun College"--P. 2.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from pdf title page (viewed on January 7, 2016).
Keywords: Industrial safety -- Textbooks; Industrial hygiene -- Textbooks; Electronic books